Longitudinal Associations Between Childhood Adversity and Adolescent Intimate Partner Violence in Malawi - Kidman, Rachel (Journal of interpersonal violence, 2023)
Adverse childhood experiences (ACEs)—including child maltreatment, witnessing violence, and household dysfunction—have been robustly associated with poor health in later life. There is also increasing evidence that those who experience childhood adversity are more likely subsequently to be victims or perpetrators of intimate partner violence (IPV). Most evidence, however, is cross-sectional and concentrated in high-income settings, and cannot be generalized to more diverse contexts. In contrast, this study assessed longitudinal relations between ACEs and IPV in a low-income country. We interviewed 1,878 adolescents in rural Malawi between 2017 and 2018 (aged 10–16) and again in 2021 (aged 13–20). Adolescents completed the Adverse Childhood Experience—International Questionnaire. Past-year physical, sexual, and emotional IPV victimization and perpetration were measured using the WHO’s Violence Against Women Instrument. We estimated multivariate regression models between cumulative adversity (0–13 adversities) at baseline and IPV at follow-up among respondents who reported any romantic or sexual partnerships. The cumulative ACEs score was associated with emotional IPV victimization for boys (OR = 1.12 per ACE) and sexual IPV victimization for girls (OR = 1.18). The ACEs score demonstrated a significant association with perpetration for girls only (OR = 1.33 for emotional IPV). By using longitudinal data, we more rigorously demonstrated the critical role of childhood adversity in shaping later IPV behavior. There are ongoing efforts toward primary prevention of childhood adversity. Given the burden that adolescents already carry (six ACEs on average in our sample), we also need secondary interventions that can help interrupt the pathway from adversity to IPV. This calls for increased collaboration between those working to address violence against children and violence against women.